SOSIAL EKONOMI ISTRI BERPERAN GANDA DI KENAGARIAN TALANG KOTO PULAI KECAMATAN RANAH AMPEK HULU TAPAN KABUPATEN PESISIR SELATAN - Anita, Syofria - (STKIP PGRI Sumbar, 2014)
Talang Koto Pulai Basa Ampek Balai Tapan subdistrict sout pesisir regency westSumatera Province is1 of 10 village in Ranah Ampek Hulu Tapan subdistrict have distance 113km from Regency city. Allong with female chacter inlife to continue change to answer challangeof period, not aside from female character to increase family is husband. But female have tocontribute active to support economicâs family.The puposes of reserch are to get data, to process, to analize and to discuss socialeconomic wife contribute double in Talang Koto Pulai village Ranah Ampek Hulu Tapansubdistrict south pesisir regency is looked at: 1) incomeâs wife contribute double, 2) Educationlevelâs wife contribute double, and 3) Time workâs wife contribute double. The type of research isdescriptive research, The population of research is house wife contribute double / work. TalangKoto Pulai village Ranah Ampek Hulu Tapan subdistrict south Pesisir regency, The sample ofresearch is taken total sampling, The sample of research amount to 135 person. Data collection isused questionmaire, Aanalysis is used statistic descriptive with formula presentation.The result of research indicate: 1) income is tee getten by wife contribute double inTalang Koto Pulai Village Ranah Ampek Hulu Tapan Subdistict south pesisir regency, a veragefee Rp. 1000.000-Rp. 1.350.000/ moon. Income is a verage fee minimum from UMR westSumatera Province Rp. 1.350.000. 2) Education levellâs wife contribute double in Talang KotoPulai Village Ranah Ampek Hulu Tapan Subdistrict sout pesisir regency e lementry school finis.3) Time worksâ wife contribute duuble in Talang Koto Pulai village Ranah Ampek Hulu Tapansubdistrict sout Pesisir Regency average society 9 hours/day.